PENERAPAN EKSPERIMEN SAINS DI RAUDHATUL ATHFAL - Eviyatul Fajriyyah; Nur Fajrie (Department of Early Childhood Education, Universitas Bina Bangsa Getsempena, 2022)
Learning science in early childhood can be done in a fun way, one of which is with science experiments. Science experiments are very important and influence the development of early childhood, especially children's ability to think critically and stimulate social-emotional development. The purpose of this research is to find out how the application of science experiments conducted at RA Tarbiyatul Athfal Kajar Dawe Kudus. A qualitative descriptive research approach is used in this study. Information collected through interviews, field observations, and documentation. Data is reduced, presented, and conclusions drawn during the data analysis process. The results of this study indicate that the application of science experiments at RA Tarbiyatul Athfal Kajar Dawe Kudus was carried out in a simple way, using materials that were easily available and even using used materials. The applied science experiment activities can stimulate aspects of social-emotional development.AbstrakPembelajaran sains pada anak usia dini dapat dilakukan dengan cara yang menyenangkan salah satu diantarnya yaitu dengan eksperimen sains. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penerapan eksperimen sains yang dilakukan di RA Tarbiyatul Athfal Kajar Dawe Kudus. Pendekatan penelitian deskriptif kualitatif digunakan dalam penelitian ini. Informasi yang dikumpulkan melalui wawancara, observasi lapangan, dan dokumentasi. Data direduksi, disajikan, dan ditarik kesimpulan selama proses analisis data. Di RA Tarbiyatul Athfal Kajar Dawe Kudus, penerapan eksperimen sains dilakukan beberapa kali selama satu semester sesuai dengan tema. Bahan yang digunakan pada eksperimen sains juga memanfaatkan bahan bekas.